Distinct checkpoint and homolog biorientation pathways regulate meiosis I in Drosophila oocytes. - Joanatta G Shapiro; Neha Changela; Janet K Jang; Jay N Joshi; Kim S McKim (PLoS Genetics)
Mitosis and meiosis have two mechanisms for regulating the accuracy of chromosome segregation: error correction and the spindle assembly checkpoint (SAC). We have investigated the function of several checkpoint proteins in meiosis I of Drosophila oocytes. Increased localization of several SAC proteins was found upon depolymerization of microtubules by colchicine. However, unattached kinetochores or errors in biorientation of homologous chromosomes do not induce increased SAC protein localization. Furthermore, the metaphase I arrest does not depend on SAC genes, suggesting the APC is inhibited even if the SAC is not functional. Two SAC proteins, ROD of the ROD-ZW10-Zwilch (RZZ) complex and MPS1, are also required for the biorientation of homologous chromosomes during meiosis I, suggesting an error correction function. Both proteins aid in preventing or correcting erroneous attachments and depend on SPC105R for localization to the kinetochore. We have defined a region of SPC105R, amino acids 123-473, that is required for ROD localization and biorientation of homologous chromosomes at meiosis I. Surprisingly, ROD removal from kinetochores and movement towards spindle poles, termed "streaming," is independent of the dynein adaptor Spindly and is not linked to the stabilization of end-on attachments. Instead, meiotic RZZ streaming appears to depend on cell cycle stage and may be regulated independently of kinetochore attachment or biorientation status. We also show that Spindly is required for biorientation at meiosis I, and surprisingly, the direction of RZZ streaming.